Differences in Creatinine and Ureum Levels 2nd Month and 3rd Month in Tuberculosis Patients of OAT Therapy - Azizah Krissan Zahra; Fitriani Kahar; Nurul Qomariyah; Anung Sugihantono; Yusriyanto; Irnawati (MultiTech Publisher, 2024)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Tuberculosis patients who test positive must undergo therapy using Anti-Tuberculosis Drugs (OAT). Treatment is divided into two phases, namely the intensive phase is carried out for 2 months with the consumption of rifampicin (R), isoniazid (H), pyrazinamide (Z), and etambutol (E) and the advanced phase is carried out for 4 months with isoniazid (H) and rifampicin (R) OAT. To find out the difference in creatinine and urea levels in the 2nd and 3rd months. Typeof research using quantitative with aprospective cohort research design. The sampling technique uses the purposive sampling method with a sample number of 15. Normality and homogeneity tests were carried out,normal distributed results were obtained and the number of samples did not meet the requirements, so the Wilcoxon statistical test was used. A total of 12 respondents (80.0%) experienced a decrease in urea levels from the 2nd month to the 3rd month. There was a differencein creatinine levels at the 2nd and 3rd months with a p-value of 0.026 (p < 0.05), butthere was no difference inthe urea levelsat the 2nd and 3rd months with a p-value of 0.201 (p < 0.05).